2022
DOI: 10.3390/genes13061000
|View full text |Cite
|
Sign up to set email alerts
|

Application of CRISPR/Cas Technology in Spermatogenesis Research and Male Infertility Treatment

Abstract: As the basis of animal reproductive activity, normal spermatogenesis directly determines the efficiency of livestock production. An in-depth understanding of spermatogenesis will greatly facilitate animal breeding efforts and male infertility treatment. With the continuous development and application of gene editing technologies, they have become valuable tools to study the mechanism of spermatogenesis. Gene editing technologies have provided us with a better understanding of the functions and potential mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…A recent study showed that intratesticular injection of VEGF can enhance spermatogenesis and decrease apoptosis in rats with varicoceles [ 31 ]. Research has demonstrated that the application of the CRISPR/Cas9 gene editing technique to silence the HIF-1 α gene in rat testes with varicoceles has an impact on the regulation of spermatogenesis in varicocele rats [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that intratesticular injection of VEGF can enhance spermatogenesis and decrease apoptosis in rats with varicoceles [ 31 ]. Research has demonstrated that the application of the CRISPR/Cas9 gene editing technique to silence the HIF-1 α gene in rat testes with varicoceles has an impact on the regulation of spermatogenesis in varicocele rats [ 32 ].…”
Section: Discussionmentioning
confidence: 99%